2019
DOI: 10.1002/macp.201900216
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a Radical‐Triggered Polymerizing High Internal Phase Emulsion into an Open‐Cellular Monolith

Abstract: The time and manner by which initially discrete cells in a high internal phase emulsion (HIPE) become highly interconnected by windows during/after polymerization (polyHIPE) remain a controversy. Water‐in‐oil HIPE with styrene/divinylbenzene as the oil phase is one of the most widely studied systems. Here, new evidence is presented on the evolution of polyHIPE with the aid of a macrosurfactant and new instruments. The macrosurfactant has a branched polyethylenimine as the hydrophilic head and polystyrene chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…The microstructure of the synthesized materials clearly depended on the amount of D 4 H added to HIPE, that is, on the V 3 polymer cross-linking degree. SEM images (Figure 1) show that only in the V3_1:1 and V3_1:1.5 samples, of higher polymer cross-linking levels, pore morphology typical of polyHIPEs [7][8][9][10][11][12][13][14][15]19 developed. In contrast, the V3_1:0.44 and V3_1:0.66 samples, of lower polymer cross-linking degrees, contained "flat", nonporous areas on their surfaces, more numerous in the case of the former than the latter one (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microstructure of the synthesized materials clearly depended on the amount of D 4 H added to HIPE, that is, on the V 3 polymer cross-linking degree. SEM images (Figure 1) show that only in the V3_1:1 and V3_1:1.5 samples, of higher polymer cross-linking levels, pore morphology typical of polyHIPEs [7][8][9][10][11][12][13][14][15]19 developed. In contrast, the V3_1:0.44 and V3_1:0.66 samples, of lower polymer cross-linking degrees, contained "flat", nonporous areas on their surfaces, more numerous in the case of the former than the latter one (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Since their first description, polyHIPEs synthesized via conventional radical copolymerization of styrene and divinylbenzene in w/o emulsions have been the focus of numerous studies. However, other monomers, polymerization methods, and/or types of emulsion have been used in HIPE templating as well. For example, ring-opening copolymerization of ε-caprolactone and a difunctional monomer (4,4-bioxepanyl-7,7′-dione) in oil-oil (o/o) HIPE has led to macroporous polyesters showing the shape memory effect .…”
Section: Introductionmentioning
confidence: 99%
“…The organic phase, St and DVB, was then polymerized to form the skeleton of the porous material [ 48 ], and the water phase was removed from the pore cavities to give the GN/PSt porous materials with high porosities and open pore structures ( Figure 2 ). As seen in the SEM images in Figure 2 a, the GN/PSt composites contained interconnected polymer walls that formed large spherical pores ( Figure 2 a), and many smaller pores were present within the polymer skeleton ( Figure 2 b) [ 49 ]. GN randomly penetrated into the matrix of the porous materials, resulting in a rougher microstructure and lower surface energy ( Figure 2 c–f) [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies suggested the role of phase separation and vacuum induction [48]. Li et al [49] suggested that pore formation is not related to vacuum and attributed it to the combination of volume contraction and surfactant migration upon gelation. Closed cellular polyHIPE is typically obtained when nanoparticles are used as the stabilizer of a HIPE system (called Pickering emulsion).…”
Section: Pei Macrosurfactant-aided Metal Nanoparticle-dictated Polyhipementioning
confidence: 99%